Resource implications of Inter-facility Transport between Emergency Departments in Hong Kong. Issue 2 (14th January 2011) - Lo, S M; Choi, K T Y; Lee, L L Y; Graham, C A; Tang, S Y H; Chan, J T S
Abstract : Background: The Inter-facility Transport (IFT) service provided by the Emergency Department (ED) is a vital service in Hong Kong. Patients need to be rapidly transported over distances to access appropriate healthcare facilities. Methods: This study aims 1. to examine the resource utilisation of IFT accompanied by ED staff and 2. to analyse the crude, fixed and variable costs of IFT. A retrospective review was conducted of all IFT from Alice Ho Miu Ling Nethersole Hospital in the New Territories of Hong Kong where ED staff accompanied patients from 1 January 2006 to 31 December 2008. Descriptive analysis was used to evaluate the crude, fixed and variable costs per year for providing an ED-based IFT service. Results: There were 337 transports accompanied by either medical or nursing staff from the ED that accounted for around 2% of all IFT. The most common indication for mobilising the transport team was an unstable clinical condition that required neurosurgical care. The average transport service time was 57.7 min per transport (SD 11.0). Resource utilisation consisted of fixed and variable costs that summed up to a cost of HKD $87 224.3 (USD $11 182.6) per year and the crude cost of providing IFT service by the ED was HKD$852.2 (USD $109.3) per patient. Conclusion: The crude cost of providing IFT service by the ED was reasonable and acceptable.